Let `x=sec(theta) `

Then

`dx=sec(theta) tan(theta) d(theta)`

When `x=1` then `theta=0`

when `x=2` then `theta=(pi/3)`

`int_1^2 (x^3)/sqrt(x^2-1)dx`

`=int_0^(pi/3)(sec^3 theta xx sec theta xx tan theta)/tan(theta)d(theta)`

`=int_0^(pi/3) sec^4 theta d(theta)`

`=int_0^(pi/3) (1+tan^2 theta)sec^2theta d(theta)`

We know that;

`(d(tantheta))/(d(theta)) = sec^2theta`

`d(tantheta) = sec^2thetad(theta)`

`int_1^2 (x^3)/sqrt(x^2-1)dx`

`= int_0^(pi/3) (1+tan^2theta)d(tantheta) ` same as `int(1+x^2)dx`

`=[tantheta+(tan^3 (theta))/3]_0^(pi/3)`

`=sqrt(3)+(3sqrt(3))/3`

`=2sqrt(3)`

*So the answer is;*

`int_1^2 (x^3)/sqrt(x^2-1)dx = 2sqrt3`

**Further Reading**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now